2020
DOI: 10.1016/j.jclepro.2020.122628
|View full text |Cite
|
Sign up to set email alerts
|

Sulfidic mine tailings and marl waste rock as compatible resources in a microwave-assisted roasting process

Abstract: Copper (Cu) is a popular commodity metal, and novel technologies are being developed to extract Cu from low-grade sources, such as sulfidic tailings. Roasting of tailings allows efficient Cu extraction and reduces environmental risks associated with tailing storage. However, conventional roasting is energyintensive and releases harmful sulfur oxide gas (SOx). This study combines two mining wastes, sulfidic tailing and carbonate-rich waste rock (marl), in an energy-efficient microwave-assisted roasting step to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 25 publications
2
25
0
2
Order By: Relevance
“…Additionally, simulating the roasting conditions as a function of temperature by HSC Chemistry software (Figure S2), it was observed that above 15 500 °C the predominant iron phase was hematite, while copper and zinc were still present as sulfates, which are known to be more soluble at mild conditions than the corresponding oxides. Finally, previous studies conducted on the roasting of sulfidic tailings from the Iberian Pyrite Belt showed that the optimal leaching efficiencies for Cu and Zn were obtained after roasting of the solid material between 500 °C and 600 °C [56]. Therefore, 550 °C was selected as the roasting temperature for this study.…”
Section: Microwave Roasting Of Sulfidic Tailingsmentioning
confidence: 99%
“…Additionally, simulating the roasting conditions as a function of temperature by HSC Chemistry software (Figure S2), it was observed that above 15 500 °C the predominant iron phase was hematite, while copper and zinc were still present as sulfates, which are known to be more soluble at mild conditions than the corresponding oxides. Finally, previous studies conducted on the roasting of sulfidic tailings from the Iberian Pyrite Belt showed that the optimal leaching efficiencies for Cu and Zn were obtained after roasting of the solid material between 500 °C and 600 °C [56]. Therefore, 550 °C was selected as the roasting temperature for this study.…”
Section: Microwave Roasting Of Sulfidic Tailingsmentioning
confidence: 99%
“…Sulfidic tailings can be classified according to their sulfur content as low (S < 5%), medium (5% < S < 20%), and high sulfur-containing tailings (S > 20%) [57]. In order to discuss general aspects of the chemical composition of sulfidic tailings, examples of the chemical compositions of medium and highly sulfidic metal tailings were collected from 18 publications, most of which address solidification/stabilization and CPB of sulfidic tailings [25,31,42,[44][45][46][47][48]50,[52][53][54][55][56][58][59][60][61]. Table 4 shows a summary of the compositions collected.…”
Section: Chemical Compositionmentioning
confidence: 99%
“…Table 6. Summary of mineral phase compositions of medium and highly sulfidic tailings obtained from the literature [12,43,44,49,50,53,54,59,61], expressed as percentages of crystalline phases. Sulfidic tailings have highly heterogeneous and deposit-specific mineralogy, which may include sulfides, silicates, oxides, hydroxides, phosphates, halides, and carbonates [5].…”
Section: Mineral Phase Compositionmentioning
confidence: 99%
See 2 more Smart Citations